Aortic thrombosis in a patient with a late diagnosis of Behcet's disease - Ana Bittencourt Detanico; Marcelo Luiz Brandão; Ly de Freitas Fernandes; Carolina Parreira Ribeiro Camelo; Juliano Ricardo Santana dos Santos (Jornal Vascular Brasileiro, 2015)
Behcet's disease is form of systemic vasculitis of unknown etiology. One surprising feature is that arterial involvement is less common in this disease than venous forms, accounting for 1 to 7% of patients. In 7 to 30% of cases the vascular symptoms precede the clinical diagnosis of Behcet. We describe the case of a patient with Thromboangiitis Obliterans who was treated with lumbar sympathectomy and an aortobiiliac bypass. Around 1 year later he was diagnosed with Behcet's disease after presenting with oral ulcers, genital ulcers and scaling lesions on the hands.